Emerging Technologies for In Vitro Inhalation Toxicology (Adv. Healthcare Mater. 18/2021). Issue 18 (22nd September 2021) - Singh, Ajay Vikram; Romeo, Anthony; Scott, Kassandra; Wagener, Sandra; Leibrock, Lars; Laux, Peter; Luch, Andreas; Kerkar, Pranali; Balakrishnan, Shidin; Dakua, Sarada Prasad; Park, Byung‐Wook
Abstract : Inhalation Toxicology In article number 2100633 by Ajay Vikram Singh, Byung‐Wook Park, and co‐workers, a systematic approach is taken to discuss the bottleneck, pros and cons of current technologies pertaining to organ‐on‐a‐chip systems for inhalation toxicology. Design processes inspired from soft robotics actuation with attention to the inhalation exposure, lung cells, and materials used are presented.